Clinical Evaluation of Various Thyroid Hormones on Thyroid Function - Hong Li; Xiaolan Yuan; Lu Liu; Jiaojiao Zhou; Chunyan Li; Peng Yang; Le Bu; Manna Zhang; Shen Qu (International Journal of Endocrinology)
To clarify the clinical value of serums total triiodothyronine (TT3), total thyroxine (TT4), free triiodothyronine (FT3), and free thyroxine (FT4) and provide a more eligible and economic strategy to assess thyroid function. A total of 2,673 participants (500 patients with hyperthyroidism, 500 patients with hypothyroidism, and 1,673 healthy people) were involved in our study. Serums TT3, TT4, FT3, and FT4 and thyrotropin (TSH) were measured with VIDAS fluorescent enzyme immunoassay. The Pearson correlation between TT3, TT4, FT3, and FT4 and TSH was determined to identify the most important indicator for thyroid function besides TSH. The correlation of TT4, and FT4 with TSH was statistically significant in healthy individuals (P < 0.01), and the R-values were −0.065 and −0.152, respectively. The correlation of TT4, FT4, TT3, and FT3 with TSH was statistically significant in patients with hyperthyroidism, and the R-values were −0.241, −0.225, −0.195, and −0.176, respectively. The correlation of TT4, FT4, TT3, and FT3 with TSH was statistically significant in patients with hypothyroidism, and the R-values were −0.322, −0.262, −0.179, and −0.136, respectively. In our opinion, TSH and FT4 are the most valuable indicators in assessing thyroid function in a healthy population, and TSH and TT4 are the most meaningful in hyperthyroidism and hypothyroidism.